To Prescribe or Not to Prescribe: A Quality Improvement Project in Improving Resident Doctors’ Confidence in Managing Acute Behavioural Disturbance - Zuhair Ahmad; Rooble Ali; Deenan Edward (BJPsych Open)
Aims: The management of acute behavioural disturbances necessitates an appreciation for the potential methods, risks, and monitoring requirements needed following assessment and initiation of management. A previous quality improvement project highlighted variability in clinicians initiating rapid tranquillisation agents in response to the same clinical vignette. This study aimed to improve Resident doctors’ confidence in deciding to use pharmacological or non-pharmacological methods in managing acute disturbance by 25%.